Mental illness and cultural issues in West African films: implications for orthodox psychiatric practice. Issue 1 (10th June 2004) - Aina, O F
Abstract : The portrayal of psychiatry and of the activities of supernatural forces in indigenous films produced in West Africa was critically examined in this study. Most often the content of these films is centred on African culture, African mythical stories, or real life events. Over a three year period, 163 such films were studied. Twenty five (15.3%) of them contained scenes of psychiatric illness. In 24 of these, there were "cases of psychoses"; and the remaining one was that of "deliberate self harm" via overdose with hypno-sedative drug. The causative factors of these "illnesses" were largely attributed to supernatural or preternatural forces. The effective treatment or "healing" of the illnesses was portrayed as arising mostly through magical means or traditional forms of care. In addition, sudden death from "spiritual attack" by these agents was shown in 35 (21.5%) of the films. Scenes of witches and occultists wreaking other forms of havoc on victims at night were shown in eight (4.9%) of the films. The implications of these films' portrayals of psychiatry and supernatural forces for the public (particularly viewers with mental illness) and for orthodox psychiatric practice in the region were highlighted.